KUALITAS PELAYANAN SUB BAGIAN UMUM DAN KEPEGAWAIAN RUMAH SAKIT UMUM DAERAH (RSUD) SUKADANA KABUPATEN LAMPUNG TIMUR - Dodi Asyadi; Sigit Setioko; Tri Widodo (Wacana Publik, 2018)
This public service is becoming increasingly important because it is always in touch with a public audience that has a diversity of interests and goals. This research was written with a descriptive qualitative approach. Data obtained through in-depth interviews, documentation data and observations. The results of the study, it can be concluded that the services of the general sub-division and staffing at Sukadana Hospital are: (1) Sometimes there are other employees who are less satisfied with the performance that has been given. (2) Being able to establish a sense of justice means that there is openness in providing services that do not discriminate and give treatment to individuals or groups of people in the same situation. (3) Can do with a fast, timely, pleasant and reliable time. (4) Economical and efficient efficient services can be reached with acceptable rates and taxes on all levels of employees in Sukadana Regional Hospital, East Lampung Regency.